Aobrigo ou de como Abrigar e Obrigar Brincam de Amarelinha nas Relações entre Educadore(a)s Sociais e Meninas em um Abrigo de Fortaleza - Olinda, Sahmaroni Rodrigues de (2011)
This text designs the process of my Master Course research and aims at reaching, from the relationship between social educators and adolescent girls at a shelter in Fortaleza, the possible changes which those characters perceive about themselves while in touch at the social shelter. From this viewpoint, I could figure out the characteristics of: the girls sent to shelter institutions; the different discourse practices that institute this “protection place” according to the ECA; the girls considered in “vulnerability situation” and the social educators whom the girls share the shelter with. From the dialogue between authors such as Paulo Freire, Michel Foucault, Giorgio Agamben, Loïc Wacquant, João Figueiredo, Leonardo Boff among other discontent thinkers, I tried to understand at what proportion the official protection reveals to be at the same time protection and punition and also question whether this protection is upon the girls or the state itself. I made use of an ethnographical methodology through the following techniques: open interview, participant observation, documental research, and data analysis from the perspective of the French Discourse Analysis (A.D.), pointing out authors like Michel Foucault and Dominique Maingueneau. This way, from some generate-words like adolescence/adolescent, shelter, vulnerability and social educator, I tried to decompose the structure of the social shelters as a place to give shelter and protection in order to understand the parallel movement of obligation and punition that institute different political practices